Exploring contrasts in food choice motives across different types of consumers of organic food: a pilot study among Malaysian adults - Jaafar, Nur Aqilah Amalina; Sulaiman, Norhasmah; Zainal Badari, Shamsul Azahari; Sabran, Mohd Redzwan (Human Resource Management Academic Research Society, 2023)
Interest in sustainability is on the rise worldwide, particularly within the food industry. This surge in interest has contributed to the growing popularity of organic food, as individuals perceive it to be advantageous for both environmental well-being and personal health. However, the consumption of organic food remains a niche practice, predominantly embraced by specific groups of people with personalized motives, particularly in developing nations. This study aims to address this issue by investigating the variations in food choice motives between regular organic food consumers and non-to-occasional organic food consumers among Malaysian adults. A total of 119 usable responses were collected through targeted online sampling, utilizing Facebook advertisements and a Google Form as the data collection tools for the study. The analysis yielded interesting findings, unveiling distinct prioritization of motives between the two consumer groups. Specifically, regular organic food consumers display greater concern for values such as risk and health factors, whereas non-to-occasional consumers prioritize practicality, placing emphasis on price and convenience. The findings of this preliminary study offer valuable insights for relevant stakeholders, enabling them to effectively support sustainability goals through food consumption. This involves a focus on the motivational factors that either encourage or hinder organic food consumption. Additionally, the study highlights the importance of understanding consumers' food choice motives in relation to their actual level of organic food consumption.